The “wrong drug” problem in anaesthesia: An analysis of 2000 incident reports - Currie, M.; Mackay, P.; Morgan, C.; Runciman, W. B.; Russell, W. J.; Sellen, Abigail; Webb, R. K.; Williamson, J. A. (Anaesthesia & Intensive Care, 1993)
Amongst the first 2000 incidents reported to the Australian Incident Monitoring Study, there were 144 incidents in which the “wrong drug” was nearly or actually administered to a patient. Thirty-three percent of the incidents involved ampoules and just over 40% syringes; in over half of the latter the syringes were of the same size, and also, in over half, they were correctly labelled. In 81% of the 144 incidents the “wrong drug” was actually given. This was more common with syringes (93%) than ampoules (58%). Thus the most common error was actually giving the wrong drug from a correctly labelled syringe. The most common drug involved was a muscle relaxant in both ampoule and syringe incidents. In 74% of all reports, there was the potential for serious harm to the patient; however no deaths were reported. Factors which contributed significantly to the incidents were similar appearance, inattention and haste. “Failure of communication” was a significant factor in syringe incidents when two or more staff were involved. The only significant factor which minimised the outcome was rechecking of the syringe or drug ampoule before giving the drug. Strategies suggested to address the “wrong drug” problem include education of staff about the nature of the problem and the mechanisms involved; colour coding of selected drug classes for both ampoules and syringes; the use of standardised drug storage, layout and selection protocols; having a drawing up and labelling convention; and the use of checking protocols.